Proceedings MEMS 98. IEEE. Eleventh Annual International Workshop on Micro Electro Mechanical Systems. An Investigation of Micr
DOI: 10.1109/memsys.1998.659769
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and surface modification process for micro gas bearing

Abstract: A hydrodynamic gas bearing able to reduce power losses is selected, and the possibility of reducing its size is examined. The first consideration is how laser-assisted etching can be employed to form spiral grooves on the cylindrical shaft. In a hydrodynamic gas bearing, the shaft and bearing come into contact with each other when the actuator is started and stopped. It is thus necessary to reduce the frictional torque during starting and to ensure a satisfactory level of wear resistance. Next, the grooved sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other gas and liquid phase LCE processes have also been exploited for MEMS fabrication. For example, laser-assisted liquid-phase KOH (potassium hydroxide) etching has been used to produce hydrodynamic bearing structures (shafts with spiral grooves) for use in rotating micromachines [24].…”
Section: Laser-assisted Etchingmentioning
confidence: 99%
“…Other gas and liquid phase LCE processes have also been exploited for MEMS fabrication. For example, laser-assisted liquid-phase KOH (potassium hydroxide) etching has been used to produce hydrodynamic bearing structures (shafts with spiral grooves) for use in rotating micromachines [24].…”
Section: Laser-assisted Etchingmentioning
confidence: 99%
“…Fabrication of metallic microstructures may be done by precision machining, electrodischarge machining, laser machining, LIGA, etc. 5 10 have shown that titanium can be effectively etched in phosphoric acid with good surface quality. Laser ablation machining of metallic microstructures, however, has limitations in precision due to high thermal and mechanical loads that can lead to thermal deformation of the processed workpiece or poor surface quality by redeposition of melt and droplets.…”
Section: Introductionmentioning
confidence: 99%